2015
DOI: 10.1136/bmjopen-2015-007947
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with induced abortion among female entertainment workers: a cross-sectional study in Cambodia

Abstract: ObjectiveTo explore risk factors associated with induced abortion among sexually active female entertainment workers (FEWs) in Cambodia.DesignCross-sectional study.SettingPhnom Penh and Siem Reap, Cambodia.ParticipantsThis study included 556 FEWs aged 18–47 years randomly selected from entertainment establishments in the two cities in 2014 using a two-stage cluster sampling method. Data were collected through face-to-face interviews using a structured questionnaire.Primary outcome measureHistory of induced abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
7
26
0
Order By: Relevance
“…Elsewhere, a study in China conducted among adolescent FSWs also found general sexual and reproductive health knowledge to be low, and while 98% reported not wanting the pregnancy, less than half (43%) reported consistent condom use with another 28% reporting current use of another contraceptive method [27]. A separate study examining contraceptive use among female entertainment sex workers in Cambodia found several factors to be linked to unwanted pregnancy such as the increase in a number of clients, inconsistent condom use, condom breakage and forced unprotected sex [28]. Elsewhere, unwanted pregnancy was more common among older married women who additionally had lower contraceptive knowledge [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, a study in China conducted among adolescent FSWs also found general sexual and reproductive health knowledge to be low, and while 98% reported not wanting the pregnancy, less than half (43%) reported consistent condom use with another 28% reporting current use of another contraceptive method [27]. A separate study examining contraceptive use among female entertainment sex workers in Cambodia found several factors to be linked to unwanted pregnancy such as the increase in a number of clients, inconsistent condom use, condom breakage and forced unprotected sex [28]. Elsewhere, unwanted pregnancy was more common among older married women who additionally had lower contraceptive knowledge [29].…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers were those related to access to the services which included fear of getting tested for HIV whenever they visited family planning clinics, competition in clinic time and time for clients, among other barriers. To increase family planning uptake among FSW in Cambodia, the government and NGOs provide free and friendly sexual and reproductive health services, despite this, some FSW still reported barriers such as discrimination by providers thereby making them resort to using of private providers [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently found that 54% of FEWs reported at least one induced abortion during their lifetime, and 33% while working as a FEW [12]. The rates of consistent condom use with commercial and non-commercial partners in the past three months were 79 and 31%, respectively [13]. Through the five years of the SAHACOM lifespan, the rates of condom use with both commercial and non-commercial partners were not appreciably improved [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, to the best of our knowledge, there is no published study that evaluates the factors associated with HIV/STI testing behaviour of heterosexual men patronising entertainment establishments (EEs) who engage in casual or paid sex. EEs are karaoke lounges, bars, pubs, nightclubs and discotheques that provide entertainment activities such as singing, dancing and social drinking [21]. In recent years, sex work has increasingly shifted from brothels to EEs, particularly in Asia [22].…”
Section: Introductionmentioning
confidence: 99%